Genetically modified bacteriophages in applied microbiology - Bárdy, P; Pantůček, R; Benešík, M; Doškař, J (Journal of applied microbiology, 2016)
Bacteriophages represent a simple viral model of basic research with many possibilities for practical application. Due to their ability to infect and kill bacteria, their potential in the treatment of bacterial infection has been examined since their discovery. With advances in molecular biology and gene engineering, the phage application spectrum has been expanded to various medical and biotechnological fields. The construction of bacteriophages with an extended host range or longer viability in the mammalian bloodstream enhances their potential as an alternative to conventional antibiotic treatment. Insertion of active depolymerase genes to their genomes can enforce the biofilm disposal. They can also be engineered to transfer various compounds to the eukaryotic organisms and the bacterial culture, applicable for the vaccine, drug or gene delivery. Phage recombinant lytic enzymes can be applied as enzybiotics in medicine as well as in biotechnology for pathogen detection or programmed cell death in bacterial expression strains. Besides, modified bacteriophages with high specificity can be applied as bioprobes in detection tools to estimate the presence of pathogens in food industry, or utilized in the control of food-borne pathogens as part of the constructed phage-based biosorbents.
Keywords: Biological Therapy; biologická terapie; Bacterial Infections; enzybiotics; průmysl zpracování potravin; biotechnologie; bakteriofágy; biosenzitivní techniky; biotechnology; genetické inženýrství; Bacteria; průmyslová mikrobiologie; pathogen detection; bacteriophages; phage therapy; Biosensing Techniques; Food-Processing Industry; bakteriální infekce; Animals; lidé; Biofilms; biopharmaceuticals; Humans; Biotechnology; zvířata; genetically modified bacteriophages; biofilmy; Industrial Microbiology; Bacteriophages; Genetic Engineering